Sucrose concentration and volume of liquid medium on the in vitro growth and development of blackberry cv. Tupy in temporary immersion systems - Ayub,Ricardo Antônio (2019)
ABSTRACT Micropropagation of small fruits such as blackberry has been employed due to the need to obtain plants with high phytosanitary quality. Bioreactor technology has been used to improve efficiency in seedling production. Thus, the objective of this work was to evaluate the best culture medium volume and sucrose concentration for blackberry micropropagation in a temporary immersion bioreactor. In vitro blackberry shoots were segmented containing two buds and an internode (1.0 cm) and placed into MS medium supplemented with inositol (0.1 g L-1), BAP (1 mg L-1) and sucrose (10, 20, 30 or 40 g L-1) at different medium volumes (150, 175 and 200 mL). The total length, number of leaves, number of shoots, and number of hyperhydric shoots were evaluated 56 days after start of the project. For blackberry development and propagation in a bioreactor system, the best results were shown at a medium volume of 175 ml and a sucrose concentration of 20 g L-1.